KETAHANAN USAHA (BUSINESS RESILIENCE) UMKM DI KOTA MANADO PADA MASA PASCA-PANDEMI COVID-19 - Saerang, Regina Trifena; Gunawan, Emilia Margareth; Wangke, Shinta Jeanette Camelia (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. MSMEs, which play an important role in the Indonesian economy, cannot be avoided from the serious impact of the COVID-19 pandemic. As a result of the decline in production and trade values, a number of workers lost their jobs. In times of crisis, many businesses have to close down as a result of restrictions in the social and economic fields. But apart from that, there are also many MSMEs that can survive and are able to get through the pandemic. Therefore, the phenomenon of business resilience is important to study and research. The aim of this research is to look at the factors that influence the resilience of a business. The focus of the research is on businesses in the MSME classification, especially in Manado City. The sampling technique is purposive sampling by determining the criteria for respondents who are MSMEs in Manado City, who have been running a business for more than 4 years. In this study, the sample size was 63 respondents. The results of this research found that Entrepreneurial Characteristics and Technological Capabilities have a significant effect on Business Resilience, while Government Support has an insignificant effect on MSME Business Resilience in Manado City in the post-pandemic period. Abstrak. UMKM yang memegang peranan penting dalam perekonomian Indonesia tak terhindarkan dari dampak serius oleh pandemi COVID-19. Akibat turunnya jumlah produksi dan nilai perdagangan, sejumlah pekerja yang kehilangan pekerjaannya. Dalam masa krisis, banyak usaha yang harus gulung tikar sebagai dampak dari pembatasan di bidang sosial dan ekonomi. Namun terlepas dari itu, banyak juga UMKM yang dapat bertahan dan mampu melewati masa pandemi. Oleh sebab itu, fenomena ketahanan usaha ini penting untuk dikaji dan diteliti. Tujuan dari penelitian ini adalah untuk melihat faktor-faktor yang mempengaruhi ketahanan suatu bisnis. Fokus penelitian adalah pada usaha dalam klasifikasi UMKM khususnya di Kota Manado. Teknik pengambilan sampel bersifat purposive sampling dengan menetapkan kriteria responden yang merupakan pelaku UMKM di Kota Manado, yang telah menjalankan bisnis selama lebih dari 4 tahun. Pada studi ini, besarnya sampel sebanyak 63 responden. Hasil dari penelitian ini menemukan bahwa Karakteristik Wirausaha dan Kapabilitas Teknologi berpengaruh signifikan terhadap Ketahanan Usaha, sedangkan Dukungan Pemerintah berpengaruh tidak signifikan terhadap Ketahanan Usaha UMKM di Kota Manado pada masa pasca-pandemi.